MARKET DYNAMISM, LEARNING ORIENTATION, FIRM INNOVATIVENESS AND FIRM PERFORMANCE: A PATH ANALYSIS - Zehir, Songul; Zehir, Melike (FUTURE ACAD, 2019)
Market dynamism means continuous uncertainty and rapid changes in the market. Dynamism in today's markets is quite high and in these circumstances, firms have to develop appropriate strategies and increase their performance to sustain their existence. This paper examines the market dynamism, shared vision-open mindedness, commitment to learning, firm innovativeness and firm performance variables relationships. The literature has studies which focus on firm innovativeness, learning orientation and firm performance. However, according to the explored Web of Science and Google Schoolar databases the relationship between these variables and market dynamism is rarely studied. Within the scope of study, a survey was conducted with 486 medium and large sized companies managers and white collar employees in Turkish manufacturing sector, in 2015. The obtained data were analyzed by SPSS and AMOS programs. Through a path model, variables direct and indirect impact on market dynamism, learning orientation, firm innovativeness and firm performance. Based on the analysis results, all the hypothesises except H3 and H8 are verified. Path and regression analyses provided two important findings. The first, firm innovativeness has full mediating effect on commitment to learning and firm performance relationship. The second, firm innovativeness has partial mediating effect on shared vision-open mindedness and firm performance relationship. (C) 2019 Published by Future Academy www.FutureAcademy.org.UK
Keywords: Market dynamism; commitment to learning; shared vision; firm innovativeness; firm performance; path analysis; ENVIRONMENTAL DYNAMISM; DETERMINANTS; INTEGRATION; MODELS; Business & Economics